(untitled) (World Bulletin of Social Sciences, 2025)
This article examines the theme of war from both philosophical and literary perspectives. It presents the views of philosophers and writers who have either condemned or justified war throughout history. The study reveals both the negative and positive aspects of war, an immortal theme that has persisted from ancient times to modern literature.